XAS and XMCD reveal a cobalt(II) imide undergoes high-pressure-induced spin crossover - Bouldi, Nadejda; Mannini, Matteo; Retegan, Marius; Miller, Reece G.; Cahier, Benjamin; Sainctavit, Philippe; Guihéry, Nathalie; Mallah, Talal; Cabaret, Delphine; Gouéré, Diane; Baudelet, François; Nataf, Lucie; et al. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2022)
The spin crossover (SCO) transition is investigated in two molecular Co2+ bis-imide compounds, Co(dpzca)2 and Co(pypzca)2 (where Hdpzca = N-(2-pyrazylcarbonyl)-2-pyrazinecarboxamide and Hpypzca = N-(2-pyrazylcarbonyl)-2-pyridinecarboxamide). They crystallize solvent-free with similar crystal structures but have been reported to exhibit different temperature-dependent magnetic behaviors. Using temperature- and pressure-dependent element selective X-ray absorption spectroscopy (XAS and XMCD) measurements, it is revealed herein that although Co(pypzca)2 does not afford a temperature-induced SCO, it undergoes a reversible pressure-induced SCO transition that is less abrupt, and is complete at a higher pressure (3.5 GPa), than for Co(dpzca)2 (0.5 GPa). Wave function-based calculations performed on isolated complexes confirm the LS state nature of Co(dpzca)2 at low temperatures, and the values of spin and orbital magnetic moments are determined. Calculations show the similarity of ground-state properties for HS Co(dpzca)2 and HS Co(pypzca)2 and the existence of a double-well HS-LS in the potential energy surface for both compounds. It is concluded that the observed, significant differences in pressure- and temperature-induced SCO transitions of Co(dpzca)2 versus Co(pypzca)2 are probably due to different intermolecular interactions between Co(dpzca)2 and Co(pypzca)2, which would hamper the temperature-induced SCO in Co(pypzca)2.